2010
DOI: 10.1111/j.1748-1716.2010.02105.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardio‐respiratory reflexes evoked by phenylbiguanide in rats involve vagal afferents which are not sensitive to capsaicin

Abstract: The present observations indicate that PBG produced tachypnoea at a lower concentration and apnoea at a higher concentration involving vagal afferents which are different from those excited by capsaicin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 20 publications
5
21
0
Order By: Relevance
“…It has been well-documented that right atrial bolus injection of phenylbiguanide (PBG), a 5-HT 3 receptor agonist, can stimulate PCFs to produce an apnea [5, 17]. In our recent study [26], we found that isoflurane (ISO), a volatile anesthetic widely used in clinics, could increase the excitability of PCFs in rats, which is supported by another study performed in dogs [21].…”
supporting
confidence: 66%
“…It has been well-documented that right atrial bolus injection of phenylbiguanide (PBG), a 5-HT 3 receptor agonist, can stimulate PCFs to produce an apnea [5, 17]. In our recent study [26], we found that isoflurane (ISO), a volatile anesthetic widely used in clinics, could increase the excitability of PCFs in rats, which is supported by another study performed in dogs [21].…”
supporting
confidence: 66%
“…As shown in Fig. 1, right atrial bolus injection of PBG induced RSB associated with bradycardia and hypotension, consistent with a previous report in rats (Dutta & Deshpande, 2010). The cardiorespiratory responses to PBG in this study were characterized by: 1) a shortened T E (−35%, from 0.40 ± 0.05 s to 0.26 ± 0.03 s, P < 0.01) with a latency of 1.88 ± 0.03 s; 2) a decreased MBP (−38%, from 88 ± 5 to 54 ± 6 mmHg, P < 0.01) and 3) a lowed HR (−40%, from 336 ± 23 to 201 ± 21 beats/min, P < 0.05).…”
Section: Resultssupporting
confidence: 92%
“…First, the production of RSB or an apnea is dependent on the stimulating intensity of PCFs. The RSB was induced by intra-atrial injection of a low dose of PBG while an apnea was also evoked if a high dose of PBG was used, and both types of responses disappeared after bilateral vagotomy (Coleridge & Coleridge, 1994; Moreira et al , 2007; Dutta & Deshpande, 2010). Second, μ-receptor agonists can excite unmyelinated C type neurons in the nodose ganglion of rabbits (Higashi et al , 1982; Crain & Shen, 1990) in vitro and stimulate PCFs to induce an apnea in vivo (Willette & Sapru, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCFs are critical in modulating respiratory frequency, and its excitatory or inhibitory impacts on respiratory frequency are dependent on the stimulating intensity on these sensory nerve endings. For example, to stimulate PCF, right atrial bolus injection of phenylbiguanide (PBG) at a low dose evokes RSB, but it at a high dose induces an apnea (Coleridge and Coleridge, 1994; Dutta and Deshpande, 2010; Moreira et al, 2007). Because μ-receptor agonists could sensitize/activate PCFs (Willette and Sapru, 1982), we previously tested whether systemic administration of μ-receptor agonist fentanyl would switch the PCFs-mediated RSB into an apnea via sensitizing PCFs (Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%